1986
DOI: 10.1902/jop.1986.57.11.672
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Titan‐S Sonic Sealer Versus Curettes in the Removal of Subgingival Calculus

Abstract: This study evaluated clinically the effectiveness of hand versus sonic subgingival scaling and root planing in the removal of calculus by visually examining the root surface at the time of periodontal flap surgery. Consideration was given to the method of instrumentation, probing depth, number of roots, and type of tooth surface. Eleven patients with moderate to advanced periodontal disease were evaluated. Four subjects were scaled and root planed with the Titan-S only, four with curettes only, and three with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
4
37
0
4
Order By: Relevance
“…Complete calculus removal following periodontal instrumentation is rare 27 . Similarly to other studies, 4,27,28 we found that 22.3% of the total surfaces evaluated were free of calculus.…”
Section: Discussionsupporting
confidence: 79%
“…Complete calculus removal following periodontal instrumentation is rare 27 . Similarly to other studies, 4,27,28 we found that 22.3% of the total surfaces evaluated were free of calculus.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have demonstrated that it is not. [23][24][25][26][27][28][29][30] This study agrees with these findings. There was residual calculus remaining after instrumentation with no significant difference between the two curets.…”
Section: Resultssupporting
confidence: 92%
“…This could account for the low percentage (3.9%) of molars extracted during active treatment. Because the mean PD (6.7 mm) exceeded the depth of effective scaling and root planing (SRP) (5 mm), surgery was done on most molars 45,46 with emphasis on thorough SRP. Conservative osseous surgery was done to remove thickened bone and to enhance flap adaptation.…”
Section: Discussionmentioning
confidence: 99%